IS IT SAFE TO E-CIGARETTE SMOKING AS ALTERNATIVE SMOKING? - Prakoso, Tegar Dwi (Majority, 2015)
Abstract E-cigarette or electronic cigarette is an electronic device that resembles a cigarette and can produce smoke as the result of evaporation of the liquid. Fluids used in the e-cigarette are generally composed of propyleneglycol, glycerol, distilled water, flavoring substances and nicotine. E-cigarette is claimed to have beneficial effects on health such as increased exercise tolerance and less coughing as the result of smoking on conventional cigarretes. However, although relatively safe, smoking remains detrimental to health. E-cigarette still contains nicotine as in conventional cigarettes that can cause addiction. So that the use of e-cigarettes on the public needs to be reevaluated. Keywords: conventional cigarette, electric cigarette, nicotine Abstrak E-cigarette atau electronic cigarette adalah alat elektronik yang mirip seperti rokok dan dapat menghasilkan asap yang merupakan hasil penguapan cairan. Cairan yang digunakan dalam e-cigarette umumnya terdiri dari propilen glikol, gliserol, air suling, zat perasadan nikotin. E-cigarette diklaim memiliki efek yang bermanfaat bagi kesehatan seperti meningkatkan toleransi latihan dan sedikit menimbulkan batuk. Namun, walaupun relatif lebih aman, merokok tetaplah merugikan bagi kesehatan. E-cigarette tetap mengandung nikotin seperti pada rokok konvensional yang dapat menimbulkan kecanduan. Sehingga penggunaan e-cigarette pada masyarakat perlu dikaji ulang. Kata kunci: rokok elektrik, nikotin, rokok konvensional